WHEN PHILOSOPHERS DISCUSS HISTORY: THE THOUGHTS OF HERMENEUTIC PHILOSOPHERS IN EXAMINING HISTORY - Mahardika, Moch. Dimas Galuh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The analysis of hermeneutics has been a subject of great interest and research among scholars, who have documented their findings in numerous books and scientific journals. In this article, the author endeavors to provide a deeper insight into hermeneutics as a tool and approach for examining the past. The ideas of prominent philosophers from the 19th and 20th centuries have contributed significantly to advancing historical research, particularly in comprehending past human activities and behaviors. Several renowned philosophers, including Dilthey, Gadamer, and Collingwood, have provided invaluable insights into interpreting and explaining history based on existing textual sources. This literature-based study seeks to explore the perspectives and discussions of these philosophers on the hermeneutic approach to interpreting history.